The Reality of Teaching Performance Faclty Members at College of Education from the Perspective of Students at Tishreen Uniersity - سومر برغل (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
The study aimedion from at recognising the reality of teaching performance of faculty members at colleges the Perspective of Students at Tishreen Uniersity, the study used a descriptive approach, the study sample consisted of (795) studentsm, a questionnaire consisting of (30) items, was applied on them and spread over four areas, nrmely; the field of preparation and planning for teaching, scientific research, measurement and evaluation, and dialogue and discussion with stuents. The results revealed that the arithmetic average of the reality of teaching performance of faculty members at colleges of education of Tishreen Uniersity as a whole amounted to (3.60), and the preparationm, the findings revealed that there were no statistically significant differences from the Perspective of Students at Tishreen Uniersity, and there were no ststistically significant differences due to the variable academic level in the areas preparation and planning to teach, and measurement and evalution differences, while there were statistically significant differences in areas; scientific research differences, dialogue and discussion with the students.